2022
DOI: 10.1177/09544089211072715
|View full text |Cite
|
Sign up to set email alerts
|

Biconvective transport of magnetized couple stress fluid over a radiative paraboloid of revolution

Abstract: In the present study, the physical features of the bioconvective MHD flow of a couple stress fluid over an upper horizontal surface (i.e. surface shaped like a submarine or any ( uhsp) aerodynamical automobile) is analysed by considering radiation and viscous dissipation effects. In the fluid-saturated domain flow is induced due to the reaction of catalytic surface, double diffusion and stretching fluid layers. In fact, couple stress fluid is electrically conducted because non-uniform magnetic field is imposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Gangadhar et al 34 discused the convective heat transfer characteristics of a hybrid nanofluid mixture with slip effects by considering Tiwari-Das nanofluid modeland and he concluded that increased slip effects greatly enhance the local heat transfer rate in the nodal and saddle point regions. Some very recent related studies can be found in [35][36][37][38][39][40][41][42][43][44] . Sharma et al 45 discussed the transfer of heat over a porous rotating disk and concluded that with the increase in the magnetic field, viscous dissipation, and the thermal radiation mechanism, the magnitude of the magnetic-fluid temperature is also increased.…”
Section: List Of Symbolsmentioning
confidence: 99%
“…Gangadhar et al 34 discused the convective heat transfer characteristics of a hybrid nanofluid mixture with slip effects by considering Tiwari-Das nanofluid modeland and he concluded that increased slip effects greatly enhance the local heat transfer rate in the nodal and saddle point regions. Some very recent related studies can be found in [35][36][37][38][39][40][41][42][43][44] . Sharma et al 45 discussed the transfer of heat over a porous rotating disk and concluded that with the increase in the magnetic field, viscous dissipation, and the thermal radiation mechanism, the magnitude of the magnetic-fluid temperature is also increased.…”
Section: List Of Symbolsmentioning
confidence: 99%
“…The use of couple stress fluid in an analysis of three-lobe journal bearing 44) improved their dynamic stability whereas an increase in critical mass and decrease in whirl frequency was observed for an improvement of stability range. The consideration of radiation and viscous dissipation effect in biconvective MHD flow analysis for couple stress fluid showed an increase in thermal boundary layer for Brinkman number and a reverse trend for concentration boundary layer 45) . On analysing the performance of journal bearing for couple stress fluid, misalignment, surface roughness and thermal effect, an enhancement in all performance characteristics was observed except side leakage for an increase in couple stress parameter 46) .…”
Section: Introductionmentioning
confidence: 98%
“…In their respective studies, Muhammad Sohail Khan et al [ 55 ], Kotha Gangadhar et al [ 56 ], and Dhanekula Naga Bhargavi et al [ 57 ] discovered that hybrid nanofluids outperform single-based nanofluids in terms of enhancing mass and thermal transfer in convection concerns. Several authors [ [58] , [59] , [60] , [61] ] conducted numerical examinations of bio-convection fluid flow problems on various geometries with different boundary conditions. Multiple researchers [ [62] , [63] , [64] , [65] , [66] ] conducted numerical investigations.…”
Section: Introductionmentioning
confidence: 99%